2016
DOI: 10.4238/gmr.15038549
|View full text |Cite
|
Sign up to set email alerts
|

Allele- and parent-of-origin-specific effects on expression of the KCNJ11 gene: A candidate for meat tenderness in cattle

Abstract: ABSTRACT. In contrast to the Mendelian inheritance model, parental alleles can contribute unequally to gene expression, which may result in phenotypic variance among individuals and bias in the predicted additive effect of molecular markers associated with production traits. Given the need to understand the effects of allelic variation and parentof-origin effects on the expression of genes with a commercial interest in cattle, we analyzed the expression of KCNJ11 (potassium inwardly rectifying channel, subfami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Those authors observed a desirable degree of meat tenderness in young Nellore animals after just 7 days of maturation. Using molecular markers, de Souza et al (2016) observed allele and parent-of-origin-specific effects on the expression of candidate genes for meat tenderness in Nellore beef cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Those authors observed a desirable degree of meat tenderness in young Nellore animals after just 7 days of maturation. Using molecular markers, de Souza et al (2016) observed allele and parent-of-origin-specific effects on the expression of candidate genes for meat tenderness in Nellore beef cattle.…”
Section: Introductionmentioning
confidence: 99%